Livedo vasculopathy: Ablation of the affected vessels to prevent recurrent ulcerations. (October 2019) - Parsi, Kurosh; Kang, Mina; Abbott, Lisa
Background: Livedo vasculopathy is a cutaneous thrombotic microangiopathy favouring the lower legs characterised by an intense reticulate pigmentation, atrophie blanche and recurrent painful stellate ulcerations. There is a strong association with antiphospholipid syndrome, thrombophilic abnormalities, factor V Leiden mutation and more recently, lipoprotein A. Thrombotic occlusion of the dermal venules is the key pathology in livedo vasculopathyand there is no associated vasculitis. Anticoagulation and other currently recommended conservative therapies do not influence the rate of ulcer healing. Method: Concurrent venous hypertension was treated with endovenous ablative methods. In addition, vessels deemed to be involved in the process of vasculopathy, irrespective of their reflux status were identified on duplex ultrasound or by sight and ablated using endovenous laser and/or sclerotherapy. Results: Five patients received endovenous intervention while two patients did not undergo any procedures. One patient requested a delay in interventions due to her circumstances and the other patient had multiple contraindications and comorbidities. On long-term follow-up, the intervention achieved complete ulcer healing and resolution of pain without any recurrence in four treated patients. Conclusion: We recommend ablative venous interventions in suitable patients with livedo vasculopathy to prevent recurrent ulcerations. Compression should be considered as an adjunct treatment.